Prevalence of freestyle biomechanical errors in elite competitive swimmers - Virag, B.; Hibberd, E. E.; Oyama, S.; Padua, D. A.; Myers, J. B. (Sports Health: A Multidisciplinary Approach, 2014)
Poor freestyle stroke biomechanics is a suggested risk factor for shoulder pain and pathology, but this has not been proven in biomechanical or clinical studies. Furthermore, the prevalence of these theoretical errors has not been identified, which would help coaches, athletic trainers, and researchers determine the most appropriate errors to focus on and develop interventions.